PENGARUH MOTIVASI TERHADAP KINERJA PEGAWAI DIKANTOR CAMAT KEPENUHAN HULU - Riza, Lisma (Jurnal Mahasiswa Prodi SI Manajemen, 2013)
Reaching officer performance for the shake of the form of required [by] organizational target [of] motivation work among pengawai. Existence of motivation of organization in meaning give motivation or motivation to [all] officers. [Gift/ giving] of motivation are process motivate [all] prgawai in such a manner so that they will work with the compliment. Motivate is is strength in x´self of seseorangyang will influence gone to direction, intensity and continuity of voluntary action to realize target which have become the target of with. This research is [done/conducted] [at] Office Sub-Regency Chief Fullness of Pate;Upstream. Population in this research is entire/all existing officer [is] office District of Fullness of Pate;Upstream counted 30 people. Method analyse isn´t it analyse simple linear regression. Pursuant to research result concluded that motivation have an effect on simultaneously to performance officer of District of Fullness of Pate;Upstream with the meaning the importance of a leader give motivation to officer [so that/ to be] the performance of becoming good.PENDAHULUAN